(untitled) (Universal xalqaro ilmiy jurnal, 2026)
This paper examines transgenerational scenarios as stable intergenerational models of the transmission of psychological attitudes, role expectations, and traumatic experiences in Central Asian families. It analyzes the influence of the collectivist cultural model on the preservation of family scenarios and their role in shaping the spiritual and moral immunity of individuals. The need to incorporate transgenerational analysis into the training of practicing psychologists in the context of educational modernization is substantiated. The risks of reproducing dysfunctional patterns and the resources for their psychological transformation are identified.